Integrated Intelligent Systems for Engineering Design - Zha, X. F; Howlett, R. J (Sage Publications Ltd, 2006)
This book aims to describe recent findings and emerging techniques that use intelligent systems (particularly integrated and hybrid paradigms) in engineering design, and examples of applications. The goal is to take a snapshot of progress relating to research into systems for supporting design and to disseminate the way in which recent developments in integrated, knowledge-intensive, and computational AI techniques can improve and enhance such support. The selected articles provide an integrated, holistic perspective on this complex set of challenges and provide rigorous research results. The focus of this publication is on the integrated intelligent methodologies, frameworks and systems for supporting engineering design activities. The subject pushes the boundaries of the traditional topic of engineering design into new areas. The book is of interest to researchers, graduate students and practicing engineers involved in engineering design and applications using integrated intelligent techniques. In addition, managers and others can use it to obtain an overview of the subject, and gain a view about the applicability of this technology to their business. As AI and intelligent systems technologies are fast evolving, the editors hope that this book can serve as a useful insight to the readers on the state-of-the-art applications and developments of such techniques at the time of compilation.